Dentists’ readiness to accept an electronic oral health surveillance system in Egypt using a modified framework of the unified theory of acceptance and use of technology (UTAUT): a cross-sectional survey - Hams H. Abdelrahman; Maha Hamza; Wafaa Essam; May Adham (BMC Oral Health)
Abstract Background Effective public health surveillance is essential for policymaking and resource allocation. The World Health Organization (WHO) supports the integration of mobile technologies to create mobile Oral (m-Oral) Health surveillance systems to enhance disease monitoring. The effectiveness and sustainability of electronic health information initiatives depend on users’ acceptance of new technologies. This research assessed dentists’ acceptance of electronic oral health surveillance systems (EOHSS) and related factors, guided by the Unified Theory of Acceptance and Use of Technology (UTAUT) model. Materials and methods A cross-sectional study included 1470 Egyptian dentists in an online survey from November 2023 to May 2024. The dentists were recruited from the five administrative regions in Egypt using convenience and snowball sampling. Participants responded to a questionnaire that was based on the UTAUT model. Structural equation model (SEM) was used for data analysis. Results 83.4% of dentists intended to use EOHSS. Performance expectancy (PE) (ß = 0.240, 95% CI: 0.182, 0.295), training adequacy (TA) (ß = 0.232, 95% CI: 0.165, 0.291), and effort expectancy (EE) (ß = 0.231, 95% CI: 0.169, 0.289) had the greatest influence on behavioral intention (BI). In contrast, anxiety towards electronic systems (ANX) (ß = -0.140, 95% CI: -0.187, -0.095) had a significant negative effect on BI. Effort Expectancy (EE) had a significantly stronger positive impact on BI of females than males. Moreover, EE had a significantly stronger impact on BI of dentists older than 40 years old than those who were younger than 30 years old. Conclusions Egyptian dentists’ intentions to use the EOHSS were influenced by PE, TA, and EE. However, anxiety related to technology may limit its adoption. EE had a greater positive impact on BI in females and in older dentists.